Pediatric type 1 cartilage tympanoplasty outcomes: A comparison of short and long term hearing results. Issue 4 (August 2018) - Kaya, Isa; Benzer, Murat; Gode, Sercan; Sahin, Furkan; Bilgen, Cem; Kirazli, Tayfun
Abstract: Objective: Tympanoplasty is a commonly used procedure in children as in adults. The purposes of this study were to evaluate and report the long term results of type 1 cartilage tympanoplasty in pediatric population. Short term and long term hearing outcomes were compared according to age and perforation location. Methods: We retrospectively evaluated a total of 76 of 93 patients who had regularly come to visits (38 male and 38 female) with chronic otitis media (COM) and who were younger than 16 years (range, 9–16 years) and underwent a primary type 1 tympanoplasty in tertiary medical center. We divided our population into 2 groups; a younger group (age <12 years) and an older group (age ≥12 years). Age, gender, follow-up time, prior to surgery and at postoperative 6th and minimum 48th month follow-up pure tone audiometry (PTA) thresholds and if any residual perforation were noted. Results: Successful closure occurred 74 in 76 patients and success rate was 97, 03%. The mean 6th month follow-up bone conduction threshold values were 7, 61 ± 3, 89 and 6, 89 ± 6, 28 <12 years old and ≥12 years old children, respectively. The mean 48th month follow-up bone conduction threshold values were 6, 93 ± 4, 00 and 7, 12 ± 6, 40, <12 years old and ≥12 years old children, respectively. The mean 6th month follow-up air conduction threshold values were 23, 75 ± 8, 38 and 24, 73 ± 10, 41 <12 years old and ≥12 years old children, respectively. The mean 48th month follow-up air conduction threshold values were 17, 15 ± 6, 04 and 20, 30 ± 10, 30, <12 years old and ≥12 years old children, respectively. Among all children; preoperative mean air conduction differed significantly from postoperative 6th and 48th month follow-up mean air conduction thresholds (p < 0.001). They had significant improvement in their ABG compared with their preoperative ABG scores. In addition according to groups, there was no significantly difference between pre and postoperative ABG improvement in both 6th and 48th month follow-up between <12 years old and ≥12 years old patient group. Conclusion: In pediatric patients type 1 tympanoplasty with cartilage graft, gives statistically significant success in long term follow up. Long term hearing results of primary type 1 cartilage tympanoplasty is seem to be better than short term hearing results as well. We consider that cartilage graft could be the best graft material for pediatric tympanoplasty for long term success.